2020
DOI: 10.1111/ajt.15787
|View full text |Cite
|
Sign up to set email alerts
|

Donor-specific chimeric antigen receptor Tregs limit rejection in naive but not sensitized allograft recipients

Abstract: Cell therapy with autologous donor-specific regulatory T cells (Tregs) is a promising strategy to minimize immunosuppression in transplant recipients. Chimeric antigen receptor (CAR) technology has recently been used successfully to generate donor-specific Tregs and overcome the limitations of enrichment protocols based on repetitive stimulations with alloantigens. However, the ability of CAR-Treg therapy to control alloreactivity in immunocompetent recipients is unknown. We first analyzed the effect of donor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 41 publications
7
96
0
2
Order By: Relevance
“…Additionally, HLA-A mismatching is commonly connected with the poor grafting result after transplantation ( 126 ). Some investigators have engineered anti-HLA-A2 CARs (A2-CARs) for Tregs, and also human A2-CAR-Tregs were assessed both in vitro and in vivo ( 139 143 ). All studies demonstrated the in vivo efficacy of CAR-Tregs in the prevention of human against mouse i.e.…”
Section: Role In Transplantationmentioning
confidence: 99%
“…Additionally, HLA-A mismatching is commonly connected with the poor grafting result after transplantation ( 126 ). Some investigators have engineered anti-HLA-A2 CARs (A2-CARs) for Tregs, and also human A2-CAR-Tregs were assessed both in vitro and in vivo ( 139 143 ). All studies demonstrated the in vivo efficacy of CAR-Tregs in the prevention of human against mouse i.e.…”
Section: Role In Transplantationmentioning
confidence: 99%
“…Trials of CAR Tregs are planned by a number of commercial enterprises; therefore, the precise details of these studies are not publicly available. Nevertheless, while enthusiasm is justified, it is not yet entirely clear whether CAR Tregs are indeed effective in humans (or whether they will be active against memory responses [77]). Moreover, their production is further complicated by the need for complex genetic modification [78], making polyclonal Tregs an attractively simple proposition if their efficacy is confirmed.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…( 104 ) In another study, compared with irrelevant CAR Tregs, donor‐specific CAR Tregs significantly delayed rejection, diminished donor‐specific antibody (DSA) levels and frequencies of DSA‐secreting B cells, and had a weaker recall DSA response after skin transplantation in a mouse model, demonstrating antigen‐specific suppression. ( 105 ) These findings signal a promising direction for the development of CAR Treg therapies to induce antigen‐specific immune suppression after LT.…”
Section: Future Prospectsmentioning
confidence: 88%